1988
DOI: 10.4039/ent120721-8
|View full text |Cite
|
Sign up to set email alerts
|

SEX PHEROMONE OF RETINIA METALLICA (BUSCK) (LEPIDOPTERA: TORTRICIDAE): IDENTIFICATION AND FIELD STUDIES

Abstract: Can. Ent. 120: 717-720 (1988) A species of the genus Monotarsobius, M. kojimai sp. nov., is described from Japan. This species is characterized by having a notable swelling on the dorsal side of tarsus I of the 15th leg in the male. ResumeOn dCcrit une espkce du genre Monotarsobius, M. kojimai sp. nov. du Japon. Cette espece est caractCrisCe par un renflement marquC de la face dorsale du tarse I de la 15bme patte du mile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…1984; Dix and Underhill 1988) (figure 2). Extensive field trials with each species have identified the most effective trap density, placement, height, and maintenance schedule, duration of trapping, attractant release rate, and attractant formulation (Dix et al , 1979(Dix et al , 1987aDix and Underhill 1988) .…”
Section: Detecting Identifying and Monitoring Outbreaksmentioning
confidence: 99%
“…1984; Dix and Underhill 1988) (figure 2). Extensive field trials with each species have identified the most effective trap density, placement, height, and maintenance schedule, duration of trapping, attractant release rate, and attractant formulation (Dix et al , 1979(Dix et al , 1987aDix and Underhill 1988) .…”
Section: Detecting Identifying and Monitoring Outbreaksmentioning
confidence: 99%